ONE OF THE BRIGHTEST LUMINARIES OF UZBEKISTAN - Tokhirova Iroda (Journals Park Publishing, 2023)
This article talks about the short life and creative work of the Russian poet and national poet of Uzbekistan-Alexander Arkadevich Feinberg. In this article, it is available to obtain an idea of not only his creative activity, but also his love for the Uzbek people and Uzbekistan.